Association of PLXND1 with a novel subtype of anomalous pulmonary venous return. Issue 9 (15th November 2021) - Zhou, Wei-Zhen; Zeng, Ziyi; Shen, Huayan; Chen, Wen; Li, Tianjiao; Ma, Baihui; Sun, Yang; Yang, Fangfang; Zhang, Yujing; Li, Wenke; Han, Bianmei; Liu, Xuewen; et al.
Abstract: Anomalous pulmonary venous return (APVR) is a potentially lethal congenital heart disease. Elucidating the genetic etiology is crucial for understanding its pathogenesis and improving clinical practice, whereas its genetic basis remains largely unknown because of complex genetic etiology. We thus performed whole-exome sequencing for 144 APVR patients and 1636 healthy controls and report a comprehensive atlas of APVR-related rare genetic variants. Novel singleton, loss-of-function and deleterious missense variants (DVars) were enriched in patients, particularly for genes highly expressed in the developing human heart at the critical time point for pulmonary veins draining into the left atrium. Notably, PLXND1, encoding a receptor for semaphorins, represents a strong candidate gene of APVR (adjusted P  = 1.1e-03, odds ratio: 10.9–69.3), accounting for 4.17% of APVR. We further validated this finding in an independent cohort consisting of 82 case–control pairs. In these two cohorts, eight DVars were identified in different patients, which convergently disrupt the GTPase-activating protein-related domain of PLXND1. All variant carriers displayed strikingly similar clinical features, in that all anomalous drainage of pulmonary vein(s) occurred on the right side and incorrectly connected to the right atrium, which may represent a novel subtype of APVR for molecular diagnosis. Studies in Plxnd1 knockout mice further revealed the effects of PLXND1 deficiency on severe heart and lung defects and cellular abnormalities related to APVR such as abnormal migration and vascular formation of vascular endothelial cells. These findings indicate the important role of PLXND1 in APVR pathogenesis, providing novel insights into the genetic etiology and molecular subtyping for APVR.